New Countries Are Applying the Harmonized System Nomenclature – Update 2011 (as of 21 June 2011) - Carsten Weerth (Global Trade and Customs Journal, 2011)
More and more countries and economic regions are applying the Harmonized Commodity Description and Coding System (Harmonized System Convention). This article examines in the update 2011 the new countries that are using the worldwide uniform language of trade since 2007 and 2008 and that are going to apply the tariff scheme from 2009, 2010, and 2011 onwards.
Additional information: Publication of Proofs according to Romeo-Policy.
Keywords: K33; K34; F53; 330; Customs Law; Harmonized System; Customs Classification; Tariff Classification; World Customs Organization; Trade Facilitiation